Coated pre-sodium-modified hard carbon negative electrode material and preparation method thereof
Through the preparation method of covering pre -sodium hard carbon negative materials, using water thermal reaction and soft carbon coating technology to solve the problem of insufficient performance of hard carbon negative materials in sodium ion batteries, and achieve efficient and safe pre -sodiumization The process improves the overall performance of the battery.
Patent Information
- Application Number
- CN202411442708.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The first-time efficiency improvement of hard carbon anode materials in existing sodium ion batteries is not obvious, the kinetic performance is poor, and the cycle life is short. The existing pre-sodiumization process is complex, unsafe and high cost, making it difficult to achieve large-scale commercial applications.
Adopt the preparation method of covering pre -sodium hard carbon negative material, obtain a hard carbon front -drive body through biomass carbon source, and match with soluble sodium salts and surface active agents under water and heat reactions to perform pre - Sodiumization treatment. Subsequently, the surface of the hard carbon material was evenly covered with a layer of soft carbon to form a soft carbon -covered pre -sodium hard carbon negative material.
Improved the first efficiency, dynamic performance and cycle life of sodium ion batteries, avoided the use of metal sodium and complex operating processes, achieved simple, efficient and safe process processes, effectively suppressing the capacity loss and structure of hard carbon electrode materials destroy.
Smart Images

Figure CN119330334A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and relates to a coated pre-sodiumized hard carbon negative electrode material and a preparation method thereof, and specifically relates to a coated pre-sodiumized hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, batteries have gradually become the main energy storage system for mobile electronic devices such as electric vehicles, mobile phones, and laptops. Lithium-ion batteries dominate various battery energy storage technologies due to their high energy density, good cycle performance, long life, and high output power. However, the limited and uneven distribution of lithium resources, coupled with the rising demand for lithium, has caused the cost of lithium batteries to soar. This cost increase, in turn, has limited the further development of the technology. Therefore, it is necessary to find products with comparable capacity and service life to lithium-ion batteries, lower cost, and better safety performance to replace lithium-ion batteries.
[0003] Sodium-ion batteries are considered to be an ideal alternative to lithium-ion batteries due to their low cost, abundant resources, and similar physical and chemical properties to lithium. As negative electrode materials for sodium-ion batteries, hard carbon materials have the advantages of large interlayer spacing and diverse structures. However, internal structural defects and sodiumization of oxygen-containing functional groups lead to irreversible capacity loss, which affects their application in sodium-ion batteries. At present, pre-sodiumization modification is the main strategy to improve the electrochemical performance of hard carbon negative electrodes. At present, pre-sodiumization technologies mainly include physical pre-sodiumization, contact pre-sodiumization, chemical reaction pre-sodiumization, and electrochemical pre-sodiumization.
[0004] Among them, physical pre-sodiumization is to roll sodium powder or sodium foil directly onto the surface of the anode sheet under a certain pressure to achieve the purpose of pre-sodiumization. However, excessive sodium powder input will promote the growth of sodium dendrites, leading to safety problems. In addition, sodium powder is highly active and prone to safety problems, making it difficult to achieve large-scale commercial application.
[0005] Contact pre-sodiumization is to place the negative electrode sheet in close contact with metallic sodium powder or sodium sheet under the wetting of electrolyte, and control the depth and uniformity of sodiumization by adjusting mechanical pressure and time. Its advantages are simple operation and controllable degree of pre-sodiumization. However, this process requires a strict water-free and oxygen-free environment, and residual metallic sodium will lead to sodium precipitation. In addition, direct contact of metallic sodium with the surface of the electrode sheet may damage the surface of the electrode sheet.
[0006] Electrochemical pre-sodiumization is to assemble a half-cell with a hard carbon anode sheet and metallic sodium first, disassemble the half-cell after a certain number of cycles or after reaching a certain potential, and then assemble the pre-sodiumized anode sheet with the cathode to finally form a complete battery. Compared with the bare anode, the pre-sodiumization treatment has a significant improvement in the performance of the whole battery. However, the complexity of the electrochemical pre-sodiumization process leads to an increase in cost, which limits its application.
[0007] There are two methods for chemical reaction pre-sodiumization: liquid phase impregnation method and chemical spray method. The liquid phase impregnation method is to immerse the hard carbon anode sheet in an ether organic solvent containing naphthalene or biphenyl to form a dense SEI film on the anode surface, thereby reducing the loss of active sodium ions in subsequent cycles and achieving pre-sodiumization. The principle of the chemical spray method is similar to the liquid phase impregnation method, except that the impregnation method is changed to a spray method. This method can effectively improve the ICE and energy density of the whole battery. However, the chemical reaction pre-sodiumization process is complicated, and the impact of by-products is unclear, which needs further study.
[0008] The above methods either involve the use of metallic sodium (which reacts easily with water and lacks operational safety), or the process is complicated and uncontrollable, and the residue of pre-sodiumization reagents will also cause capacity loss and structural damage to the electrode material, limiting the effective improvement of the performance of the electrode material. Therefore, in order to improve the charge and discharge efficiency, specific capacity and cycle stability of sodium-ion batteries, it is urgent to develop a new, simple and efficient hard carbon pre-sodiumization process. Summary of the invention
[0009] Technical issues to be solved
[0010] In order to avoid the shortcomings of the prior art, the present invention proposes a coated pre-sodiumized hard carbon negative electrode material and a preparation method, and provides a new and efficient pre-sodiumized hard carbon negative electrode material and a preparation method, so as to solve the problems in the prior art that the sodium ion battery with hard carbon as the negative electrode has no obvious improvement in the first efficiency, poor kinetic performance and short cycle life. By improving the hard carbon pre-sodiumization process, the obtained sodium ion battery has the characteristics of high first efficiency, excellent kinetic performance and long cycle life. This pre-sodiumization process avoids the direct use of metallic sodium and complicated operation processes, and provides a simple, efficient and safe process flow, while effectively suppressing the capacity loss and structural damage of the hard carbon electrode material, providing a new solution for the application of sodium ion batteries.
[0011] Technical Solution
[0012] A method for preparing a coated pre-sodiumized hard carbon negative electrode material, characterized by the following steps:
[0013] Step 1: crushing the biomass carbon source using a crusher to obtain a powdered biomass carbon source;
[0014] Step 2: placing the powdered biomass carbon source into a graphite tank and calcining it in an inert gas atmosphere at 500-800° C. to obtain a hard carbon precursor;
[0015] Step 3: adding a hard carbon precursor, a surfactant and a soluble sodium salt into an alcohol solution and stirring the mixture to obtain a pre-sodium solution;
[0016] Step 4: hydrothermally react the pre-sodium solution at 150° C. to 200° C. for 5 h, then wash, centrifuge, and dry to obtain a pre-sodium precursor;
[0017] Step 5: Add the pre-sodium precursor and the soft carbon material into a toluene solution in a mass ratio of 7.0-10.0:0.5-1.5, heat and stir for 2 hours, and then centrifuge and dry to obtain a blank;
[0018] Step 6: In an inert gas atmosphere, heat the blank to 1100°C-1300°C at a rate of 5°C / min, and keep it warm for 4-6 hours to obtain a soft carbon-coated pre-sodiumized hard carbon negative electrode material.
[0019] The biomass carbon source is one of coconut shell, bagasse, straw, wood chips, rice husk and bamboo, or a mixture of two or more of them in any proportion.
[0020] The soft carbon material is selected from petroleum asphalt, coal-based asphalt, petroleum coke or needle coke.
[0021] The surfactant is poloxamer F127, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer P123 or hexadecyltrimethylammonium bromide.
[0022] The soluble sodium salt is sodium molybdate, sodium citrate or sodium alginate.
[0023] The mass ratio of the hard carbon precursor, surfactant and soluble sodium salt is 8.0-10.0:1.0-2.0:3.0-5.0.
[0024] The inert gas includes nitrogen, argon or nitrogen and argon and any ratio of inert gases.
[0025] A hard carbon negative electrode for a sodium ion battery obtained by the preparation method is characterized in that a layer of soft carbon is uniformly coated on the surface of the hard carbon material to form a hard carbon precursor that has been pre-sodiumized and coated with soft carbon, thereby preventing direct contact between the hard carbon and the electrolyte, thereby improving the overall performance of the battery.
[0026] An application of a hard carbon negative electrode for a sodium ion battery, characterized in that: as the negative electrode of the sodium ion battery; the negative electrode of the sodium ion battery has a total battery capacity of 361.9 to 360.5 mAh g at a current density of 20 mA / g -1 , initial efficiency ICE85.5~82.1%, reversible capacity after 300 cycles 307.5~292.1mAh g -1 .
[0027] Beneficial Effects
[0028] The present invention proposes a coated pre-sodiumized hard carbon negative electrode material and a preparation method, which realizes the in-situ supplementation of a large amount of sodium source by pre-sodiumizing the hard carbon material, thereby improving the first coulombic efficiency. Under the hydrothermal reaction conditions, a higher temperature is used to promote Na + It moves to oxygen-containing functional groups and defect sites, and finally stores them in oxygen-containing functional groups and defect sites through surface adsorption, effectively reducing irreversible capacity loss and improving the pre-sodium effect, thereby improving the first efficiency of hard carbon negative electrode materials. In addition, a layer of soft carbon is evenly coated on the surface of the hard carbon material. The soft carbon coating layer can hinder the direct contact between the hard carbon and the electrolyte, enhance the stability of the hard carbon negative electrode material, and further improve the first efficiency.
[0029] The main innovative points of the present invention are:
[0030] (1) It requires only a small amount of equipment, a tubular furnace and a reactor, and the operation steps are simple and convenient;
[0031] (2) Pre-sodiumization is carried out by reacting the hard carbon precursor with a soluble sodium salt coordination complex solution, which effectively improves the first coulombic efficiency and cycle capacity retention rate;
[0032] (3) Under hydrothermal reaction conditions, a higher temperature is used to promote Na + It moves to the oxygen-containing functional groups and defect sites, and is finally stored in the oxygen-containing functional groups and defect sites through surface adsorption force, which effectively reduces the loss of irreversible capacity and thus improves the initial efficiency of the hard carbon negative electrode material.
[0033] (4) Soft carbon coating is used to evenly coat a layer of soft carbon on the surface of the hard carbon material. The soft carbon coating can hinder the direct contact between the hard carbon and the electrolyte, thereby enhancing the cycle stability of the hard carbon negative electrode material and the battery.
[0034] (5) The coated pre-sodiumized hard carbon negative electrode material prepared by the inventive method can effectively improve the charge and discharge efficiency, specific capacity and cycle life of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Comparison chart of the first cycle charge and discharge curves of Examples 1 to 3 and the prepared hard carbon material DETAILED DESCRIPTION
[0036] Now, in combination with the embodiments,
[0037] The accompanying drawings further describe the present invention:
[0038] A coated pre-sodiumized hard carbon negative electrode material and a preparation method thereof, comprising the following steps:
[0039] Step 1: crush the biomass carbon source using a crusher to obtain a powdered biomass carbon source. The biomass carbon source is one or a mixture of any proportion of coconut shell, bagasse, straw, wood chips, rice husk, and bamboo.
[0040] Step 2: Place the powdered biomass carbon source into a graphite tank and perform initial calcination at 500-800° C. in an inert gas atmosphere to obtain a hard carbon precursor.
[0041] Step 3: Add the hard carbon precursor, surfactant and soluble sodium salt obtained in step 2 into the alcohol solution in a mass ratio of (8.0-10.0):(1.0-2.0):(3.0-5.0), stir evenly, and obtain a pre-sodium solution.
[0042] Step 4: The pre-sodium solution is hydrothermally reacted at 150° C. to 200° C. for 5 hours, and then washed, centrifuged, and dried to obtain a pre-sodium precursor.
[0043] Step 5: Add the pre-sodium precursor obtained in step 4 and the soft carbon material in a mass ratio of (7.0-10.0): (0.5-1.5) to a toluene solution for heating and stirring for 2 hours, and then centrifugally dry to obtain a blank. The soft carbon material is at least one selected from petroleum asphalt, coal-based asphalt, petroleum coke and needle coke.
[0044] Step 6: The blank obtained in step 5 is heated to 1100°C to 1300°C at a rate of 5°C / min under an inert gas atmosphere, and kept warm for 4 to 6 hours to obtain a soft carbon-coated pre-sodiumized hard carbon negative electrode material.
[0045] The surfactant is at least one of poloxamer (F127), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) or hexadecyltrimethylammonium bromide.
[0046] The soluble sodium salt is at least one of sodium molybdate, sodium citrate and sodium alginate.
[0047] The alcohol solution is a mixed solution of ethanol and water in a volume ratio of (1.0-1.5):(1.5-2.5).
[0048] The inert gas includes helium, argon or a mixture of helium and argon in any proportion.
[0049] In order to make the technical solutions and advantages of the present invention more clearly described, the present invention is further described in conjunction with embodiments. It is particularly noted that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0050] Embodiment 1:
[0051] Step 1: Grind the coconut shell into powder using a grinder.
[0052] Step 2: The coconut shell powder is initially calcined at 500° C. in an argon atmosphere to obtain a hard carbon precursor.
[0053] Step 3: Dissolve 1.6 g of hard carbon precursor, 0.2 g of hexadecyltrimethylammonium bromide and 0.6 g of sodium molybdate in a mixed solution of 30 mL of deionized water and 20 mL of ethanol, stir evenly, and obtain a pre-sodium solution.
[0054] Step 4: The pre-sodium solution was subjected to hydrothermal reaction at 200° C. for 5 h, centrifuged at 7000 r / min for 5 min, washed with deionized water and ethanol, and dried at 80° C. overnight to obtain a pre-sodium precursor.
[0055] Step 5: Add 2.5 g of the pre-sodium precursor obtained in step 4 and 0.3 g of petroleum asphalt into 20 mL of toluene solution, heat and stir for 2 h, then centrifuge at 7000 r / min for 5 min, and dry at 80° C. for 5 h to obtain a blank.
[0056] Step 6: The blank obtained in step 5 is heated to 1200° C. at a rate of 5° C. / min under an argon atmosphere and kept warm for 5 hours to obtain a soft carbon-coated pre-sodiumized hard carbon negative electrode material.
[0057] Embodiment 2:
[0058] This embodiment provides a method for pre-sodiumization of hard carbon materials, except that the hard carbon material is directly obtained without being coated with soft carbon.
[0059] Step 1: Grind the coconut shell into powder using a grinder.
[0060] Step 2: The coconut shell powder is initially calcined at 800° C. in an argon atmosphere to obtain a hard carbon precursor.
[0061] Step 3: Dissolve 2.0 g of hard carbon precursor, 0.3 g of P123 and 0.9 g of sodium citrate in a mixed solution of 30 mL of deionized water and 18 mL of ethanol, stir evenly, and obtain a pre-sodium solution.
[0062] Step 4: The pre-sodium solution was subjected to hydrothermal reaction at 180° C. for 5 h, centrifuged at 7000 r / min for 5 min, washed with deionized water and ethanol, and dried at 80° C. overnight to obtain a pre-sodium precursor.
[0063] Step 5: The pre-sodium precursor obtained in step 4 is heated to 1300° C. at a rate of 5° C. / min under an argon atmosphere and kept at this temperature for 4 h to obtain a pre-sodium hard carbon negative electrode material.
[0064] Embodiment 3:
[0065] This embodiment provides a method for soft carbon coating of hard carbon materials, the difference being that the soft carbon coating is directly performed without pre-sodium treatment.
[0066] Step 1: Grind the coconut shell into powder using a grinder.
[0067] Step 2: The coconut shell powder is initially calcined at 700° C. in an argon atmosphere to obtain a hard carbon precursor.
[0068] Step 3: Add 2.1 g of the hard carbon precursor obtained in step 2 and 0.15 g of petroleum coke into 20 mL of toluene solution, heat and stir for 2 h, then centrifuge at 7000 r / min for 5 min, and dry at 80° C. for 5 h to obtain a blank.
[0069] Step 4: The blank obtained in step 3 is heated to 1100° C. at a rate of 5° C. / min under an argon atmosphere and kept at this temperature for 6 hours to obtain a soft carbon-coated hard carbon negative electrode material.
[0070] In order to reflect the improvement of the performance of the hard carbon negative electrode material in the embodiment, a method for preparing the hard carbon material is provided, except that the hard carbon material is not pre-sodiumized and soft carbon coated.
[0071] Step 1: Grind the coconut shell into powder using a grinder.
[0072] Step 2: The coconut shell powder is initially calcined at 600° C. in an argon atmosphere to obtain a hard carbon precursor.
[0073] Step 3: The hard carbon precursor obtained in step 2 is heated to 1300° C. at a rate of 5° C. / min under an argon atmosphere and kept at this temperature for 6 hours to obtain a hard carbon negative electrode material.
[0074] The sodium ion half-cells assembled with the hard carbon materials prepared in Examples 1 to 3 were subjected to charge and discharge tests at a current density of 20 mA / g to obtain the total capacity, first cycle coulomb efficiency (ICE) and cycle capacity of the sodium ion half-cell. The results are shown in Table 1. Figure 1 It is a comparison chart of the first cycle charge and discharge curves of Examples 1 to 3 and the prepared hard carbon material.
[0075] Table 1 is a comparison of the effect data of Examples 1 to 3 and the counterexample
[0076]
Claims
1. A method for preparing a coated pre-sodiumized hard carbon negative electrode material, characterized in that Here are the steps: Step 1: crushing the biomass carbon source using a crusher to obtain a powdered biomass carbon source; Step 2: placing the powdered biomass carbon source into a graphite tank and calcining it in an inert gas atmosphere at 500-800° C. to obtain a hard carbon precursor; Step 3: adding a hard carbon precursor, a surfactant and a soluble sodium salt into an alcohol solution and stirring the mixture to obtain a pre-sodium solution; Step 4: hydrothermally react the pre-sodium solution at 150° C. to 200° C. for 5 h, then wash, centrifuge, and dry to obtain a pre-sodium precursor; Step 5: Add the pre-sodium precursor and the soft carbon material into a toluene solution in a mass ratio of 7.0-10.0:0.5-1.5, heat and stir for 2 hours, and then centrifuge and dry to obtain a blank; Step 6: In an inert gas atmosphere, heat the blank to 1100°C-1300°C at a rate of 5°C / min, and keep it warm for 4-6 hours to obtain a soft carbon-coated pre-sodiumized hard carbon negative electrode material.
2. The method for preparing the coated pre-sodiumized hard carbon negative electrode material according to claim 1, characterized in that: The biomass carbon source is one of coconut shell, bagasse, straw, wood chips, rice husk and bamboo, or a mixture of two or more of them in any proportion.
3. The method for preparing the coated pre-sodiumized hard carbon negative electrode material according to claim 1, characterized in that: The soft carbon material is selected from petroleum asphalt, coal-based asphalt, petroleum coke or needle coke.
4. The method for preparing the coated pre-sodiumized hard carbon negative electrode material according to claim 1, characterized in that: The surfactant is poloxamer F127, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer P123 or hexadecyltrimethylammonium bromide.
5. The method for preparing the coated pre-sodiumized hard carbon negative electrode material according to claim 1, characterized in that: The soluble sodium salt is sodium molybdate, sodium citrate or sodium alginate.
6. The method for preparing the coated pre-sodiumized hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the hard carbon precursor, surfactant and soluble sodium salt is 8.0-10.0:1.0-2.0:3.0-5.
0.
7. The method for preparing the coated pre-sodiumized hard carbon negative electrode material according to claim 1, characterized in that: The alcohol solution is a mixed solution of ethanol and water in a volume ratio of 1.0-1.5:1.5-2.
5.
8. The method for preparing the coated pre-sodiumized hard carbon negative electrode material according to claim 1, characterized in that: The inert gas includes nitrogen, argon or nitrogen and argon and any ratio of inert gases.
9. A sodium ion battery hard carbon negative electrode obtained by the preparation method according to any one of claims 1 to 8, characterized in that: A layer of soft carbon is uniformly coated on the surface of the hard carbon material to form a hard carbon precursor that has been pre-sodiumized and coated with soft carbon, which hinders the direct contact between the hard carbon and the electrolyte, thereby improving the overall performance of the battery.
10. An application of the hard carbon negative electrode for sodium ion batteries according to claim 9, characterized in that: As the negative electrode of the sodium ion battery; the total capacity of the battery reaches 361.9 to 360.5 mAh g at a current density of 20 mA / g -1 , initial efficiency ICE 85.5~82.1%, reversible capacity after 300 cycles 307.5~292.1mAh g -1 .
Citation Information
Cited By
Sodium supplementing method of sodium ion battery hard carbon negative electrode material
CN121215765A